Evaluation of the efficacy of an exercise program for pregnant women with low back and pelvic pain: a prospective randomized controlled trial - Ortabag, Tulay; Ozdemir, Serpil; Bebis, Hatice; Acikel, Cengizhan (WILEY, 2015)
AimTo evaluate the effect of exercise programs on pregnant women with pregnancy-related low back and pelvic pain. BackgroundLow back and pelvic pain during pregnancy is a major health problem due to its frequent occurrence and such pain can limit pregnant women in many of their daily activities. DesignA randomized trial with a control group (n=48) and an intervention group (n=48). Trial registration number NCT02189356. MethodsDepartment of Obstetrics and Gynecology, between December 2011-May 2012, an Education and Research Hospital in Turkey. Based on the intention-to-treat principle, all pregnant women were analysed according to the group they were assigned to, regardless of whether they received the intervention or not. Participants in the intervention group received health counselling and exercised regarding low back and pelvic pain for four weeks. The pregnant women in the control group received usual care, comprised of routine clinical practice for pregnancy-related low back and pelvic pain. ResultsAccording to Mann-Whitney U test analysis results, there was a statistically significant difference between the control and intervention groups' Visual Analogue Scale during relaxation scores and Visual Analogue Scale during activity scores at the end of the study. According to Mann-Whitney U test analysis results, the change in the mean Oswestry Disability Index score for the intervention group and the difference in the mean scores between the two groups was statistically significant. ConclusionsA four-week exercise program including individualized health counselling to relieve low back and pelvic pain improved the functional status in pregnant women.
Keywords: pregnancy-related low back and pelvic pain; exercise program; nurse